Oxidative stress and mitochondrial dysfunction play a role in myelodysplastic syndrome development, diagnosis, and prognosis: A pilot study. (September 2015) - Gonçalves, A. C.; Cortesão, E.; Oliveiros, B.; Alves, V.; Espadana, A. I.; Rito, L.; Magalhães, E.; Lobão, M. J.; Pereira, A.; Nascimento Costa, J. M.; Mota-Vieira, L.; Sarmento-Ribeiro, A. B.
Abstract The imbalance between reactive oxygen species (ROS) production and their elimination by antioxidants leads to oxidative stress. Depending on their concentration, ROS can trigger apoptosis or stimulate cell proliferation. We hypothesized that oxidative stress and mitochondrial dysfunction may participate not only in apoptosis detected in some myelodysplastic syndrome (MDS) patients, but also in increasing proliferation in other patients. We investigated the involvement of oxidative stress and mitochondrial dysfunction in MDS pathogenesis, as well as assessed their diagnostic and prognostic values. Intracellular peroxides, superoxide, superoxide/peroxides ratio, reduced glutathione (GSH), and mitochondrial membrane potential (Δψmit) levels were analyzed in bone marrow cells from 27 MDS patients and 12 controls, by flow cytometry. We observed that all bone marrow cell types from MDS patients had increased intracellular peroxide levels and decreased GSH content, compared with control cells. Moreover, oxidative stress levels were MDS subtype— and risk group—dependent. Low-risk patients had the highest ROS levels, which can be related with their high apoptosis; and intermediate-2-risk patients had high Δψmit that may be associated with their proliferative potential. GSH levels were negatively correlated with transfusion dependency, and peroxide levels were positively correlated with serum ferritin level. GSH content proved to be an accurate parameter to discriminate patients from controls. Finally, patients with high ROS or low GSH levels, as well as high superoxide/peroxides ratio had lower overall survival. Our results suggest that oxidative stress and mitochondrial dysfunction are involved in MDS development, and that oxidative stress parameters may constitute novel diagnosis and/or prognosis biomarkers for MDS.